2018
DOI: 10.1503/cmaj.180290
|View full text |Cite
|
Sign up to set email alerts
|

Care setting and 30-day hospital readmissions among older adults: a population-based cohort study

Abstract: BACKGROUND: Despite the fact that many older adults receive home or longterm care services, the effect of these care settings on hospital readmission is often overlooked. Efforts to reduce hospital readmissions, including capacity planning and targeting of interventions, require clear data on the frequency of and risk factors for readmission among different populations of older adults. METHODS:We identified all adults older than 65 years discharged from an unplanned medical hospital stay in Ontario between Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 15 publications
1
21
0
2
Order By: Relevance
“…Adding to previous knowledge is our identification of older adults living at home with home care before admission as having increased odds of early hospital readmission, as compared to those living in the community not depending on help from the municipality or living in nursing homes. Previous research concurs with a variation in proportion of readmission when considering the care setting before and after hospitalisation [42,43] but these studies are mainly focused on the discharge destination whereas we show the importance of considering the care setting before admission. Older adults living in the community with home care are often debilitated and, even though generally not as frail as those living in nursing homes, in need of supervision and help in daily activities.…”
Section: Discussionsupporting
confidence: 86%
“…Adding to previous knowledge is our identification of older adults living at home with home care before admission as having increased odds of early hospital readmission, as compared to those living in the community not depending on help from the municipality or living in nursing homes. Previous research concurs with a variation in proportion of readmission when considering the care setting before and after hospitalisation [42,43] but these studies are mainly focused on the discharge destination whereas we show the importance of considering the care setting before admission. Older adults living in the community with home care are often debilitated and, even though generally not as frail as those living in nursing homes, in need of supervision and help in daily activities.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to a previous study on the DICARES-M,23 24% of the patients in the current study experienced emergency readmission within 30 days after their hospitalisation (table 1). This is nearly double the percentage among 700 000 patients (mean age=78 years) in a large-scale study of hospital readmissions in Canada 42. However, it is only four percentage points higher than the 20% found among 11 million beneficiaries of the Medicare Fee-For-Service model (a hospital insurance programme) in the USA 43.…”
Section: Discussionmentioning
confidence: 80%
“…It is likely that having home services allows the older adult to stay at home longer. Studies have shown conflicting results: some identify home service to be a cost-effective way to reduce readmission rates [ 43 ], whereas others led to more ED visits [ 44 ] needing better matching of recipient needs and home service provision [ 45 ]. From our study, home service uptake is poor across both groups.…”
Section: Discussionmentioning
confidence: 99%